Cellulose acetate fibres loaded with daptomycin for metal implant coatings. (15th January 2022) - Faria, Jaime; Dionísio, Bruno; Soares, Íris; Baptista, Ana Catarina; Marques, Ana; Gonçalves, Lídia; Bettencourt, Ana; Baleizão, Carlos; Ferreira, Isabel
Abstract: Multifunctional polymeric coatings containing drug delivery vehicles can play a key role in preventing/reducing biofilm formation on implant surfaces. Their requirements are biocompatibility, good adhesion, and controllable drug release. Although cellulose acetate (CA) films and membranes are widely studied for scaffolding, their applications as a protective coating and drug delivery vehicle for metal implants are scarce. The reason is that adhesion to stainless steel (SS) substrates is non-trivial. Grinding SS substrates enhances the adhesion of dip-coated CA films while the adhesion of electrospun CA membranes is improved by an electrosprayed chitosan intermediate layer. PMMA microcapsules containing daptomycin have been successfully incorporated into CA films and fibres. The released drug concentration of 3 × 10 −3 mg/mL after 120 min was confirmed from the peak luminescence intensity under UV radiation of simulated body fluid (SBF) after immersion of the fibres.